A Recent Volcanic Eruption Discovered on the Central Mariana Back-Arc Spreading Center - Chadwick, William W.; Merle, Susan G.; Baker, Edward T.; Walker, Sharon L.; Resing, Joseph A.; Butterfield, David A.; Anderson, Melissa O.; Baumberger, Tamara; Bobbitt, Andra M. (Frontiers in Earth Science, 2018)
The first known historical eruption on the Mariana back-arc spreading center was discovered during exploration of the southern back-arc for new hydrothermal vent sites in December 2015. A water-column survey along the axis of the back-arc showed hydrothermal plumes over the site characterized by low particle concentrations and relatively high reduced chemical anomalies. A dive with the autonomous underwater vehicle Sentry collected high-resolution (1-m) multibeam sonar bathymetry over the site, followed by a near-bottom photographic survey of a smaller area. The photo survey revealed the presence of a pristine, dark, glassy lava flow on the seafloor with no sediment cover. Venting of milky hydrothermal fluid indicated that the lava flow was still warm and therefore very young. A comparison of multibeam sonar bathymetry collected by R/V Falkor in December 2015, to the most recent previous survey of the area by R/V Melville in February 2013, revealed large depth changes in the same area, effectively bracketing the timing of the eruption within a window of less than three years. The bathymetric comparison shows the eruption produced a string of lava flows with maximum thicknesses of 40 m to 138 m along a distance of 7.3 km (from latitude 15° 22.3’ to 15° 26.3'N) between depths of 4050 to 4450 mbsl. The cross-axis width of the lava flows is 200-800 m. The Sentry bathymetry shows that the new lava flows are constructed of steep-sided hummocky pillow mounds and are surrounded by older flows with similar morphology. In April and December 2016, two dives were made on the new lava flows by remotely operated vehicles Deep Discoverer and SuBastian. The pillow lavas have many small glassy buds on the steep flanks of the mounds, locally thick accumulations of hydrothermal sediment near the tops of mounds, and small cones of radiating pillows at their summits. The 2015-2016 observations show a rapidly declining hydrothermal system on the lava flows, suggesting that the eruption had occurred only months before its discovery in December 2015.